2022
DOI: 10.31744/einstein_journal/2022ao6258
|View full text |Cite
|
Sign up to set email alerts
|

Needs of family members of patients in a coronary care unit

Abstract: Objective: To identify the need of family members of patients hospitalized in a coronary intensive care unit and their degree of satisfaction with the care provided. Methods: An observational and cross-sectional study including family members of patients hospitalized in the coronary intensive care unit for acute coronary syndrome in Killip I or II. After the second visit of the same family member to the patient in the unit, a 43-item inventory of needs and stressors of family members was applied. Family member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In previous studies, the most important need of the families of patients admitted to the coronary intensive care were related to assurance and information (Coelho et al, 2022). Family presence and participation were found to be helpful in reducing the patients' anxiety, improving communication (Coelho et al, 2022) and stabilising haemodynamic and respiratory indicators, such as blood pressure, pulse rate and respiratory rate (Lolaty et al, 2014); this was also found to be effective in reducing ventilator withdrawal time and complications due to positive pressure (Safaeepour et al, 2017). Haemodynamic and respiratory indicators such as blood pressure, pulse rate, respiratory rate, in the ICU are essential for preventing organ failure by ensuring stability between oxygen delivery and demand in the relevant tissues (Majumdar, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the most important need of the families of patients admitted to the coronary intensive care were related to assurance and information (Coelho et al, 2022). Family presence and participation were found to be helpful in reducing the patients' anxiety, improving communication (Coelho et al, 2022) and stabilising haemodynamic and respiratory indicators, such as blood pressure, pulse rate and respiratory rate (Lolaty et al, 2014); this was also found to be effective in reducing ventilator withdrawal time and complications due to positive pressure (Safaeepour et al, 2017). Haemodynamic and respiratory indicators such as blood pressure, pulse rate, respiratory rate, in the ICU are essential for preventing organ failure by ensuring stability between oxygen delivery and demand in the relevant tissues (Majumdar, 2017).…”
Section: Introductionmentioning
confidence: 99%